2017
DOI: 10.1103/physreve.96.062203
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Lorenz oscillators near the Hopf boundary: Multistability, intermingled basins, and quasiriddling

Abstract: We investigate the dynamics of coupled identical chaotic Lorenz oscillators just above the subcritical Hopf bifurcation. In the absence of coupling, the motion is on a strange chaotic attractor and the fixed points of the system are all unstable. With the coupling, the unstable fixed points are converted into chaotic attractors, and the system can exhibit a multiplicity of coexisting attractors. Depending on the strength of the coupling, the motion of the individual oscillators can be synchronized (both in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The basins of attraction of system (1) can be obtained by changing the parameter q and the initial conditions x(i) and y(i) in a range of (−5, 5) with the system parameters unchanged [40][41][42][43][44] as shown in Fig. 10.…”
Section: Basins Of Attractionmentioning
confidence: 99%
“…The basins of attraction of system (1) can be obtained by changing the parameter q and the initial conditions x(i) and y(i) in a range of (−5, 5) with the system parameters unchanged [40][41][42][43][44] as shown in Fig. 10.…”
Section: Basins Of Attractionmentioning
confidence: 99%
“…In compliance with this, in a recent study 24 , the authors have reported the advent of chimera states due to the presence of nonisochronicity term in a diffusively coupled global network of Rössler oscillators. They also found that the presence of multistability [25][26][27][28][29][30][31][32] is the key mechanism for the appearance of coexisting states. Moreover, the emergence of chimera state in a star network of Rössler oscillators with nonisochronicity term is demonstrated with various coupling topologies 33 .…”
Section: Introductionmentioning
confidence: 98%
“…Since both synchronized and desynchronized motions are possible on these attractors, the system exhibits chimeric behavior. The basins of attraction in such systems were found to be interwoven and riddled [54] with multiplicity of coexisting attractors [58].…”
Section: Introductionmentioning
confidence: 99%